Uczestnictwo w polityce jako moralna powinność obywatela - Sobuś, ks. Paweł Bogumił (Annales. Etyka w Życiu Gospodarczym, 2008)
According to the Aristotelian definition, politics is a co-formation of social life within humancapacity in the conditions of freedom and equality, while under specific authority. In a more narrowsense, it is understood as the art of administration. In a broader sense, it denotes any care for public life.Every citizen, as a member of a community, takes advantage of goods it has produced.Their participation cannot resemble the situation of a person subjected to a transfusion; instead, it mustmanifest itself in their contribution to the development of society.One of the aspects of the commitment to social life is political activity. It should not limit itself tothe activity of politicians themselves, but, to a greater or lesser extent, it should engage all citizens.It is by their participation in political elections that citizens undertake an effort of shaping reality.The formation of the young generation’s attitudes is another manner in which parents and teachersmanifest their care for social life.